The effects of enhancing angiotensin converting enzyme in myelomonocytes on ameliorating Alzheimer’s-related disease and preserving cognition - Danziger, Ron; Fuchs, Dieu-Trang; Koronyo, Yosef; Rentsendorj, Altan; Sheyn, Julia; Hayden, Eric Y.; Teplow, David B.; Black, Keith L.; Fuchs, Sebastien; Bernstein, Kenneth E.; Koronyo-Hamaoui, Maya (Frontiers in Physiology, 2023)
This review examines the role of angiotensin-converting enzyme (ACE) in the context of Alzheimer’s disease (AD) and its potential therapeutic value. ACE is known to degrade the neurotoxic 42-residue long alloform of amyloid β-protein (Aβ42), a peptide strongly associated with AD. Previous studies in mice, demonstrated that targeted overexpression of ACE in CD115+ myelomonocytic cells (ACE10 models) improved their immune responses to effectively reduce viral and bacterial infection, tumor growth, and atherosclerotic plaque. We further demonstrated that introducing ACE10 myelomonocytes (microglia and peripheral monocytes) into the double transgenic APPSWE/PS1ΔE9 murine model of AD (AD+ mice), diminished neuropathology and enhanced the cognitive functions. These beneficial effects were dependent on ACE catalytic activity and vanished when ACE was pharmacologically blocked. Moreover, we revealed that the therapeutic effects in AD+ mice can be achieved by enhancing ACE expression in bone marrow (BM)-derived CD115+ monocytes alone, without targeting central nervous system (CNS) resident microglia. Following blood enrichment with CD115+ ACE10-monocytes versus wild-type (WT) monocytes, AD+ mice had reduced cerebral vascular and parenchymal Aβ burden, limited microgliosis and astrogliosis, as well as improved synaptic and cognitive preservation. CD115+ ACE10- versus WT-monocyte-derived macrophages (Mo/MΦ) were recruited in higher numbers to the brains of AD+ mice, homing to Aβ plaque lesions and exhibiting a highly Aβ-phagocytic and anti-inflammatory phenotype (reduced TNFα/iNOS and increased MMP-9/IGF-1). Moreover, BM-derived ACE10-Mo/M cultures had enhanced capability to phagocytose Aβ42 fibrils, prion-rod-like, and soluble oligomeric forms that was associated with elongated cell morphology and expression of surface scavenger receptors (i.e. CD36, Scara-1). This review explores the emerging evidence behind the role of ACE in AD, the neuroprotective properties of monocytes overexpressing ACE and the therapeutic potential for exploiting this natural mechanism for ameliorating AD pathogenesis.